The application of the principle of primacy of judgment on the merits in the new Brazilian Code of Civil Procedure (Revista do Tribunal Regional Federal da 3ª Região, 2016)
Civil procedure must be studied, ordered, applied, disciplined and interpreted on the basis of the rules contained in the Federal Constitution. This is stated in Article 1 of the new CPC. The provision is obvious. Not only procedural rules, but any other must be constructed and interpreted in accordance with the Constitution of the Republic. There are several rules in the Federal Constitution that include procedural precepts. The fundamental constitutional rules apply to the process. Article 1 of the CPC refers to "norms" established in the Constitution. The expression is appropriate, covering both constitutional rules and principles. Norma is a genus of which rules and principles are species. The Constitution contains both rules and principles. Among the fundamental norms of the process, the principle of the primacy of the judgment on the merits, highlighted in this essay, stands out.
Keywords: CPC 2015; principle of primacy of judgment on the merits; application